Revisiting autonomy and attributions: a case in a Malaysian University - Nurjanah Mohd Jaafar,; Thang, Siew Ming (Penerbit UKM, 2013)
Contradictions often occur when concepts that originated in the West are applied in other contexts. Such is the case when concepts like autonomy and attributions are introduced in the context of language education in Asia. The claim that autonomy is universally applicable is refuted when researchers revealed findings which indicate that some Asian learners appear more teacher-dependent than autonomous. In the case of attributions, the claim that people in general credit themselves for successful outcomes (self-enhancing bias) and blame others for poor outcomes (ego-protective bias) appears to contradict findings that revealed some Asian learners have the opposite pattern of attributions, namely self-critical tendency. Such contradictions suggest the need to consider a number of factors like social, cultural and political when interpreting such concepts. Studies undertaken in the Malaysian context propose students‟ socio-cultural backgrounds as the reason behind their general tendencies to be teacher-centred and self-critical in the learning of English. They suggest that societies that nurture its members to respect teachers may produce self-critical learners. However, no empirical study has been undertaken to establish the relationship between autonomy and attributions in the Malaysian context. This study is an effort to bridge this gap in knowledge. A questionnaire survey was administered to 169 students of a Malaysian public university and its findings revealed their general tendencies to be both teacher-centred and self-critical. Difference in proficiency levels has some minor influence on autonomy and attributions, and the relationship between them.